Comparing ageing and the effects of diet supplementation in wild vs. captive antler flies, Protopiophila litigata. Issue 12 (26th August 2019) - Mautz, Brian S.; Rode, Nicolas O.; Bonduriansky, Russell; Rundle, Howard D.
Abstract: Few studies have simultaneously compared ageing within genetically similar populations in both laboratory and natural environments. Such comparisons are important for interpreting laboratory studies, because factors such as diet could affect ageing in environment‐dependent ways. Using a natural population of antler flies ( Protopiophila litigata ), we conducted separate factorial experiments in 2012 and 2013 that compared age‐specific male survival and mating success in laboratory cages versus a natural field environment while supplementing their diets with protein or sugar. We found consistent and substantial increases in both survival and mating rates in the laboratory compared to the field, but remarkably, despite these large differences actuarial ageing was only higher in the laboratory than in the field in 2012 and similar in the two environments in 2013. In both years, there was no difference between environments in reproductive ageing. We found that males fed protein had a higher mortality rate than males fed sugar (strong and low support in 2012 and 2013, respectively). In contrast, diet did not strongly impact average mating rates, actuarial ageing or reproductive ageing in either experiment. Our results provide the first evidence that the negative effect of protein on life span reported in many laboratory studies can also occur in wild populations, although perhaps less consistently. They also highlight how laboratory environments can influence life‐history traits and suggest caution when extrapolating from the laboratory to the field. Abstract : We address a fundamental assumption in ageing research: Can laboratory experiments act as a proxy for a natural environment? Using the antler fly, we show that the laboratory environment strongly influences average life span and mating rate, but laboratory conditions and diet manipulation have more nuanced effects on ageing.